Artificial Intelligence in Metabolomics for Disease Profiling: A Machine Learning Approach to Biomarker Discovery - Qureshi, Muhammad Danial Ahmad; Ramzan, Muhammad Fahid; Amjad, Fatima; Haider, Naeem (Indus Journal of Bioscience Research, 2024)
With an emphasis on the identification of biomarkers for pancreatic cancer, this research investigated the use of artificial intelligence (AI) and machine learning (ML) in metabolomics for disease profiling. With the use of the Kaggle dataset "Pancreatic Cancer Urine Biomarkers," which comprises 591 samples from diverse patient cohorts, we examined the connections between distinct proteome and metabolomic markers and their diagnostic value. Plasma CA19-9, LYVE1, REG1B, REG1A, and TFF1 were among the key biomarkers that were assessed in order to create a prediction model that could differentiate between benign cases, healthy controls, and pancreatic ductal adenocarcinoma (PDAC). According to our findings, the XGBoost classifier performed much better than conventional statistical techniques, recognizing positive instances with 89% accuracy and 91% sensitivity. The research also demonstrated the intricate relationships between several biomarkers that affect diagnostic accuracy and emphasized the crucial significance of the REG1B/REG1A ratio as a new predictor. We verified our model’s robustness and generalisability across various patient demographics using a thorough validation procedure that included cross-validation and sensitivity analysis. "This work demonstrates how artificial intelligence can revolutionize metabolomics, opening the door to more accurate illness characterization and individualized treatment plans. In order to enhance early identification and outcomes of pancreatic cancer and other associated disorders, our results ultimately support the use of machine learning techniques into clinical practice.